2008
DOI: 10.1007/s00421-008-0923-3
|View full text |Cite
|
Sign up to set email alerts
|

Core temperature differences between males and females during intermittent exercise: physical considerations

Abstract: We examined differences in dynamic heat balance between males and females during intermittent exercise. Six males (M) and six females (F) performed three 30-min bouts of exercise (Ex1, Ex2, Ex3) at a constant rate of metabolic heat production (M - W) of approximately 500 W separated by three 15-min periods of inactive recovery. Rate of total heat loss (M - W) was measured by direct calorimetry, while M - W was determined by indirect calorimetry. Esophageal (T (es)) was measured continuously. Exercise at a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 20 publications
0
54
0
Order By: Relevance
“…In such a design, with males and females exercising at a similar relative intensity % _ VO 2peak ; males will often produce more heat than females, since their aerobic capacity and body mass are typically greater. Accordingly, this greater heat production will lead to greater sweating in males (Gagnon et al 2008(Gagnon et al , 2009). Nevertheless, it has been shown that males produce significantly more sweat than females during exercise, even when differences in aerobic capacity between them are not evident Frye and Kamon 1983;Keatisuwan et al 1996;Kenny and Jay 2007).…”
Section: Introductionmentioning
confidence: 97%
“…In such a design, with males and females exercising at a similar relative intensity % _ VO 2peak ; males will often produce more heat than females, since their aerobic capacity and body mass are typically greater. Accordingly, this greater heat production will lead to greater sweating in males (Gagnon et al 2008(Gagnon et al , 2009). Nevertheless, it has been shown that males produce significantly more sweat than females during exercise, even when differences in aerobic capacity between them are not evident Frye and Kamon 1983;Keatisuwan et al 1996;Kenny and Jay 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Briefly, women are less capable of dissipating excess heat when performing physical work in a hot environment because of higher body fat and lower sweat rates than men. For the same job task, women will show a greater increase in heat load (Gagnon et al 2009). It has also been suggested that this effect may be slightly exacerbated during the luteal phase of the menstrual cycle because of hormonal fluctuations affecting central thermoregulatory centers (Inoue et al 2005).…”
Section: Sex Differences In Response To Environmental Extremesmentioning
confidence: 99%
“…This allowed us to assess the ability of the individuals to dissipate heat during exercise using core temperature responses (9, 14, 19). This methodology has been utilized by others when examining thermoregulatory differences between sexes, individuals of varying ages, fitness levels, and body weights (2, 9, 14, 19). Core temperature increased to the greatest extent in those with >40% BSA grafted (Figure 1), and those with 17-40% BSA grafted tended to have a greater increase in core temperature relative to Controls, but this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…An additional factor contributing to the lack of consistency regarding the effect of skin grafts on thermoregulation is likely related to methodological controls (5, 28). Given that increases in core temperature during exercise depend upon the balance between the rate of metabolic heat production and the rate of heat dissipation, it is important to clamp the rate of metabolic heat production between individuals when comparisons are made between groups (14, 19). With metabolic heat production controlled, any differences in core temperature can more precisely be attributed to differences in heat dissipation (i.e., thermoregulation).…”
Section: Introductionmentioning
confidence: 99%